3-Bromo-1, 1, 1-trifluoro-2-propanol assisted chemical fixation of CO2 and epoxides. Issue 11 (12th March 2020) - Ma, Hui; Zeng, Ji-jun; Tu, Dong-huai; Mao, Wei; Zhao, Bo; Wang, Kuan; Liu, Zhao-tie; Lu, Jian
Graphical abstract: Highlights: 3-Bromo-1, 1, 1-trifluoro-2-propanol was proved to be an excellent hydrogen-bonding donor for CO2 transformation. Synergistic effects of hydroxyl group and iodide anion render the reaction performing at 0.5 MPa CO2 . The reaction could be carried out under solvent- and metal-free conditions. A broad scope of cyclic carbonates could be obtained in high yield. Abstract: 3-Bromo-1, 1, 1-trifluoro-2-propanol (3-BTFP) in combination with n- butylammonium iodide (TBAI) was proved to be an efficient organocatalyst for chemical fixation of CO2 with various epoxides to the respective cyclic carbonates. A possible reaction mechanism was proposed wherein 3-BTFP activated epoxide through hydrogen bonding interaction. This mechanism is revealed by the results of FT-IR spectra and 1 H NMR titration, and the synergetic effect functioned by 3-BTFP and TBAI ensures the reaction proceeding effectively. Herein, 3-BTFP represents a commercially available, stable and metal-free hydrogen-bonding donor for CO2 transformation, which has a potential application for the large-scale synthesis of cyclic carbonates.